Editorial (Cadernos de Sociomuseologia, 2022)
The present issue of Cadernos de Sociomuseologia brings together a set of texts from the perspective of education, participation and heritage in the field of museology. The texts presented deal with museum and educational processes, museum education and heritage education, in museums, museum institutions and other spaces of memory and culture. The discussions presented here are based, for the most part, around two axes. First, specific case studies, providing an overview of different initiatives, which have a vision of heritage whose support is in the participation of communities, both in the definition and in its uses. In another aspect, investigations are presented that deal with broader facets of heritage, such as accessibility, participation and ways of recognizing and approaching diversity. All these themes, however, converge to a broad perspective, which recognizes heritage and its uses, by individuals and institutions, from a comprehensive conception of participation, which seeks partnerships and has its support in the desires and challenges of the communities where these heritages are inserted. The idea of ​​social participation of the communities involved and the search for a social function that gives meaning to the existence of museums and museological institutions are one of the bases shared in these researches, and some of the main paths that Sociomuseology has followed, with great interest, throughout of its trajectory.